Evaluation of relative frequency of geographic tongue and fissured tongue in psoriatic patients - F Khozeimeh; M Akhavan Taheri (Isfahan University of Medical Sciences, 2009)
Introduction: Tongue is one of the most important organs that may be involved through multiple manifestations in some of the systemic diseases such as psoriasis. This study was performed to measure frequency of geographic Tongue and fissured tongue in psoriatic patients and also to determine the relationship of sex, age, duration of disease and some other variables with these anomalies.Methods and Materials: In this descriptive- cross sectional study, 138 psoriatic patients (79 men, 59 women) were examined. Examination was done in natural light. The results were analyzed with chi-square statistic test and SPSS software.Results: The results of this study showed that 39.85% of psoriatic patients had geographic tongue, 23.91% had fissured tongue and 4.34% had both.Conclusion: The results of this study showed significant differences with other studies. The prevalence of Geographic tongue was more in women than men, but the difference was not significant. With increasing age, the prevalence of geographic tongue increased with significant difference. Also there was significant relationship between prevalence of geographic tongue and duration of disease, rate of skin involvement and the history of hospitalization. On the other hand, fissured tongue was more common in men than women, but the difference was not significant. Also fissured tongue had no relationship with other variables. Key words: Geographic tongue, fissured tongue, psoriasis